The prevention of intrapartum HIV/Aids transmission from mother to child - L Roets (AOSIS, 2003)
The transmission of HIV/AIDS from mother to child is the main cause of HIV/AIDS in children and child mortality. Two-thirds of children with HIV/AIDS are infected in the intrapartum period (Farley, 2000:1-2). Midwives, through effective practices, can lower the transmission of HIV/AIDS from mother to child in the intrapartum period. The aim of the study was to determine which preventive practices registered midwives in provincial labour wards in Bloemfontein, implement to lower the risk of mother to child transmission of HIV/AIDS and in doing so to lower child mortality.